Wakaf dalam Perspektif Fiqh: Analisis Komparatif Mazhab dan Relevansinya di Era Kontemporer - Wijayanti Eka Suryandari; Rifaldi Ahmad; Agung Nasir; Basaria Nainggolang; Marwa (Al-Kindi, 2026)
Waqf is a socio-religious institution in Islam that plays a strategic role in developing the welfare of the community. This article analyzes waqf from a fiqh perspective using a comparative approach between schools of thought, covering the definition, legal basis, pillars, conditions, types, and differences of opinion among classical and contemporary scholars. This research uses a normative legal research method with a comparative-school approach and a conceptual approach. Through a study of the Qur'an, hadith, authorized fiqh books, contemporary fatwas, and laws and regulations, this study finds that differences in views between schools, especially regarding the ownership status of waqf assets, the permanence of waqf objects, and the permissibility of cash waqf, stem from differences in istinbath methodology. The findings indicate that the flexibility of waqf fiqh, particularly in the Hanafi and Maliki schools of thought, opens up space for innovation in productive waqf management in the modern era. This article recommends a revitalization of waqf fiqh that is responsive to contemporary challenges without abandoning the fundamental principles of sharia